88 Prevalence Of SARS-COVID-19 Serum Igg Antibodies Amongst Staff on An Acute Surgical Unit. (4th May 2021) - Isheerwood, J; Winyard, J; Bekhyat Karki, B; Chung, W Y; Layton, G; Issa, E; Garcea, G; Dennison, A
Abstract: Background: The United Kingdom now has one of the highest death rates from COVID 19, with over 40, 000 deaths (1). It has been posited that the identification of care workers with immunity or increased resistance could be important in developing future strategies. Method: This was a retrospectively conducted survey of general surgical staff at a tertiary surgical unit. Results: We surveyed 215 staff that had undergone antibody testing. Of the 175/215 who reported contact with COVID-19 positive patients, 6/215 had a positive PCR result and 15/215 reported a positive antibody test. Only 3/6 that had a positive PCR test demonstrated antibodies. Conclusions: Our "immunity" rate of 7% is extremely low and is concerning especially in respect of the anticipated "herd immunity" which would mitigate many of the issues presently being confronted and it is likely to be many months at least before this makes realistic contribution. Continued testing for the presence of COVID-19 antibodies will contribute to crucial seroprevalence data that can be used by public health bodies whose advice will necessarily evolve as increasing data sets become available.